Assessing diversity index of contaminant fungi in traditional home-made salted fish: Implications for public health in a tropical setting - THASNIATY, Rahmah; SARI LUBIS, Syafrina; HARAHAP, Diannita; DJAFAR, Tasliati; IQHRAMMULLAH, Muhammad (Nutrición Clínica y Dietética Hospitalaria, 2024)
Introduction: Fungal contamination poses a significant threat to the quality of salted fish products, leading to both economic losses and health concerns. The aim of this study is to elucidate the profile of contaminant fungi in traditional home-made salted fishes and assess their diversity index. Methods: Samples of salted fish were collected from Lhok Seudu, Aceh Besar, Indonesia, following approximately three months of storage. The samples were salted barred queenfish (Scomberoides tala), red snapper (Lutjanus compchanus), and blackfin snapper (Lutjanus buncanella). After diluted to a 10-6 concentration, the sample was inoculated onto potato dextrose agar media for 5-7 days of incubation. Grown fungal colonies were enumerated, and distinct macroscopic variants were isolated for further analysis, with subsequent incubation periods of 5-7 days. Observations encompassed both macroscopic and microscopic characteristics of the fungi. Results: The findings suggested that the appearance of Aspergillus species, such as Aspergillus flavus, Aspergillus niger, and Aspergillus fumigatus, was prevalence. The diversity index of contaminant fungi in the salted fish products was 1.15, categorized as having moderate diversity. Conclusion: Indonesian public health authorities should maintain a heightened awareness of the potential threat posed by mycotoxins in traditional home-made salted fish.